1998
DOI: 10.1016/s0990-7440(98)89007-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenous and phosphorous waste production in a flow-through land-based farm of European seabass ()

Abstract: A study on nitrogenous and phosphorous waste production in European seabass (Dicentrarchus labrax) was carried out in a flow-through land-based farm. The main objectives were (i) to calculate nitrogenous (N) and phosphorous (P) waste production (particulate and dissolved) from in situ measurements for different rearing ponds with specific fish biomasses, fish sizes and flow rates, (ii) to establish nitrogenous and phosphorous waste production budgets, ratios and equations, and (iii) to compare, for the whole f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 15 publications
6
28
1
1
Order By: Relevance
“…This result was achieved on the basis of a model parameterization, which, for 18 over 19 parameters, was carried out based on experimental studies of the physiology and nutrition of this species. N and P contents in fish tissues, which were calculated by closing the budgets, compare well with those reported by Lemarié et al (1998), with respect to D. labrax, 1.4% N and 0.6% P on a wet weight basis. The fact that our results were consistent with these numbers can be seen as an indirect indication that the model is likely to simulate fish metabolism with accuracy.…”
Section: Virtual Model Of a Farmed Populationsupporting
confidence: 82%
“…This result was achieved on the basis of a model parameterization, which, for 18 over 19 parameters, was carried out based on experimental studies of the physiology and nutrition of this species. N and P contents in fish tissues, which were calculated by closing the budgets, compare well with those reported by Lemarié et al (1998), with respect to D. labrax, 1.4% N and 0.6% P on a wet weight basis. The fact that our results were consistent with these numbers can be seen as an indirect indication that the model is likely to simulate fish metabolism with accuracy.…”
Section: Virtual Model Of a Farmed Populationsupporting
confidence: 82%
“…6) In general, however, it should be noted that the FCR for mitten crab, irrespective of the feed type used was considerably higher (therefore, poorer rate of food conversion) than those recorded for finfish farming practices (Lemarié et al 1998;Gross et al 2000;Yi et al 2003;Phan et al 2009;Bunlipatanon et al 2014), and or for shrimp farming practices around the world (Hopkins et al 1993;Briggs and Funge-Smith, 1994;Thakur and Lin, 2003;Sahu et al 2013). It is therefore evident that considerable improvements have to be brought about in commonly used feeds and feed management in mitten crab culture.…”
Section: Feed Types and Feed Managementmentioning
confidence: 99%
“…A range of environmental effects has been related to net-pen aquaculture, particularly in regard to energy and nutrient fluxes, pelagic and benthic biomass and community structure, fish stocks, sedimentation rates, oxygen depletion and shifts in the algal community. Many of these are directly related to nutrient pollution, and several studies have shown that 70 to 80% of nutrients added in aquaculture are lost to the environment in the form of metabolic waste, faeces and uneaten food fragments (Kaushik 1998, Lemarié et al 1998, Lupatsch & Kissil 1998. The deposition of particulate matter from aquaculture net-pens has been identified as the main cause of negative environmental impacts (Gowen et al 1991, Pillay 1992, Read & Fernandes 2003.…”
Section: Introductionmentioning
confidence: 99%